Inventory standardization of children depression scale for adolescents aged 12 and 17 years of age, the municipality of Sabaneta, Antioquia Department, Colombia (2010)
This study is descriptive, analytic and transversal. It is a directive to the Children Depresion Inventory CDI for the diagnosis of depresion in children and adolescents, between 12 and 17 years old, scholarized in public and private school of the Municipality of Sabaneta In the Metropolitan Area of the Antioquia Department- Colombia. The Size Of the population was of 1450 people with a total of aplplied test in 583 children and youngsters. The phycometric instrument used was the CDI and realized a pilot test, this test was made indicating that the instrument is reliable and valid to evaluate and inf ere depression problems. These items has a high reliabety level for each of the variables and global scale; finding an ALFA of 0.7949 which indicates that the reactives are really designed to measure symtoms of children depression with in the studied population.